A relação educação e trabalho na legislação educacional brasileira: política pública, contexto econômico e social - Stênico, Joselaine Andréia de Godoy [UNESP] (Universidade Estadual Paulista (Unesp), 2014)
This thesis is dedicated to studying the intricacies of relationship education and work in the context of Brazilian society, theoretically arguing with several authors, especially with Marx, Gramsci, Friedmann, Naville and Braverman. The research evaluates the theoretical movement of training and employment considering the contemporary as part of a public debate tensioned by the new international requirements and national policies visualized from the 1990s. The investigation took a qualitative approach, guided by the Library Research, Document Analysis and Content Analysis. From the analysis, reflection and discussion we can achieve, the main results are: From the most rudimentary processes of vocational education to the robust and modern procedures today, the Brazilian educational system remains with the dual concept of education, although actions were undertaken in an attempt to overcome school play between manual and intellectual work, anyway, this were not enough, they have been stifled by political, social or educational reasons. Furthermore, we found that professional education has always been geared to the substrates of society for teaching a craft anchored in the separation of manual labor and intellectual labor. Another interesting result is that it was possible to bring together the key words used in the Brazilian legislation on professional education, pointing to a language predominantly related to the business world, moreover, most of the policies developed in the 1990s until the validity period refer to parties political PSDB and PT. The idea that such parties have differences in educational proposals is mere speculation, it is a supposed antagonism and continuities of proposals in the educational field. Based on data collected from large national databases was possible to outline the main characteristics of the Brazilian professional education, moreover, despite official documents show evidence that its purpose is to develop...

Esta dissertação dedica-se a estudar os meandros da relação educação e trabalho no contexto da sociedade brasileira, discutindo teoricamente com diversos autores, especialmente com Marx, Gramsci, Friedmann, Naville e Braverman. A pesquisa avalia o movimento teórico da formação e do emprego considerando a contemporaneidade como parte de um debate público tensionado pelas novas exigências internacionais e pelas políticas nacionais visibilizadas a partir da década de 1990. A investigação assumiu uma abordagem qualitativa, norteado pela Pesquisa Bibliográfica, Análise Documental e Análise de Conteúdo. A partir das análises, reflexões e debates que conseguimos realizar, os principais resultados são: Desde os processos mais rudimentares da educação profissional até os procedimentos robustos e modernos da atualidade, o sistema educacional brasileiro permanece com a concepção dual de educação, embora ações foram empreendidas na tentativa de superar a reprodução escolar entre o trabalho manual e o intelectual, mesmo assim, não foram suficientes, pois foram sufocadas ora por razões políticas, sociais ou pedagógicas. Além disso, foi possível identificar que a educação profissional sempre esteve voltada aos substratos da sociedade para o ensino de um ofício ancorado na separação do trabalho manual e do trabalho intelectual. Outro resultado interessante é que foi possível reunir os principais vocábulos utilizados na legislação brasileira de educação profissional, apontando para uma linguagem predominantemente relacionada ao mundo empresarial, além disso, grande parte das políticas desenvolvidas nas décadas de 1990 até o período em vigência se referem aos partidos políticos PSDB e PT. A ideia de que tais partidos apresentam diferenças nas propostas educacionais é mera especulação, trata-se de um suposto antagonismo e de continuidades de propostas no campo educacional. A partir de dados coletados...
Keywords: Education; Educação; Politicas publicas; Adolescentes - Emprego; Educação - Brasil; Ensino profissional; Pesquisa bibliografica